A dynamic programming approach to manage virtual machines allocation in cloud computing - Ouammou, Abdellah; Hanini, Mohamed; Ben Tahar, Abdelghani; El Kafhali, Said (International Journal of Engineering and Technology, 2018)
As a result of the dynamic nature of Virtual Machine allocation in cloud computing, it is not easy to manage system resources or choose the best configuration based solely on human experience.  In this work, we used stochastic modelling instead of comprehensive experiments to evaluate the best resource management of the system. In such complex systems, choosing the best decision is a challenge, for this reason we have designed a heuristic algorithm, specifically, dynamic programming as a resource management and programming tool that finds a way that attempts to satisfy the conflicting objectives of high performance and low power consumption. As a scenario for using this algorithm, we addressed the problem of virtual machine allocation, a subset of physical machines is designated as "reserve", and the reserves are actives when the number of jobs in the system is sufficiently high. The question is how to decide when to activate the reserves. The simulation results demonstrated the benefit of using our framework to identify the policy for consolidation or for a low energy consumption and in order to have a good quality of service in the system.
Keywords: Dynamic Programming; Cloud Computing; Management resources; Value Iteration; Stochastic Modeling.